PERAN PANCASILA SEBAGAI FILSAFAT HUKUM DALAM PEMBENTUKAN PERATURAN PERUNDANG-UNDANGAN - Natsir, Muhammad Khaidir Kahfi (CENDERAWASIH CONSTITUTIONAL REVIEW, 2025)
This research discusses the role of Pancasila as a philosophy of law in the formation of legislation in Indonesia. As a rule of law state, Indonesia recognizes Pancasila as the Grundnorm that underlies all legislation. Pancasila functions not only as a fundamental norm but also as a source of values that reflect the character of the Indonesian nation. This study employs a qualitative approach to explore the meanings and in-depth understanding of the application of Pancasila in the legal context. Through document analysis and literature review, this research identifies how the values of Pancasila are integrated into the formation of laws and their impact on society. The findings indicate that Pancasila plays a crucial role in producing laws that are just, socially equitable, and responsive to the needs of the community. Thus, Pancasila as a philosophy of law should serve as a guideline in every legislative process to achieve the state's goals based on justice and welfare for all Indonesian people.